Orientation and Stability of Asymmetric Magnetic Reconnection X Line. Issue 6 (22nd June 2018) - Liu, Yi‐Hsin; Hesse, M.; Li, T. C.; Kuznetsova, M.; Le, A.
Abstract: The orientation and stability of the reconnection x line in asymmetric geometry is studied using three‐dimensional (3‐D) particle‐in‐cell simulations. We initiate reconnection at the center of a large simulation domain to minimize the boundary effect. The resulting x line has sufficient freedom to develop along an optimal orientation, and it remains laminar. Companion 2‐D simulations indicate that this x line orientation maximizes the reconnection rate. The divergence of the nongyrotropic pressure tensor breaks the frozen‐in condition, consistent with its 2‐D counterpart. We then design 3‐D simulations with one dimension being short to fix the x line orientation but long enough to allow the growth of the fastest growing oblique tearing modes. This numerical experiment suggests that reconnection tends to radiate secondary oblique tearing modes if it is externally (globally) forced to proceed along an orientation not favored by the local physics. The development of oblique structure easily leads to turbulence inside small periodic systems. Key Points: The orientation of asymmetric reconnection x line is studied using large 3‐D particle‐in‐cell simulations Companion 2‐D simulations indicate that the 3‐D system selects a state of, or at least near, the maximal reconnection rate The system tends to radiates secondary oblique tearing modes when the primary x line is forced to misalign with this optimal orientation